Europe's white spots : postcolonial readings of eurocentrism and Nordic minority literatures - Rantonen, Eila (Tampere University dissertations, ISSN 2490-0028, 2021)
Abstract.
Keywords: kirjallisuudentutkimus; kirjallisuus; kerronta; vähemmistöt; etniset vähemmistöt; kansalliset vähemmistöt; maahanmuuttajat; postkolonialismi; kulttuurierot; litteraturvetenskap; litteratur; berättande; minoriteter; etniska minoriteter; nationella minoriteter; invandrare; postkolonialism; kulturskillnader; Pohjoismaat; Eurooppa; Norden; Europa